Enriching Students’ Multicultural Vocabulary Knowledge through the Language of Advertising on YouTube Commercial Videos - Zubaidi, Zubaidi; Maulidiyah, Fitrotul; Suharto, Ririn Pratiwi; Putri, Aulia Nourma Putri (Universitas Islam Malang, 2024)
One of the most crucial language aspects which the students should master is vocabulary. Students of D4 English for Business and Professional Communication, State Polytechnic of Malang with a restricted vocabulary are likewise limited in their listening, speaking, reading and writing abilities. It is difficult to learn a language without first acknowledging the vocabulary. Because of their restricted vocabularies, the students are unable to converse properly with one another. Eventually, with the help of various YouTube commercial videos, students could possibly work using their smartphones, tablets, or laptops while observing and analyzing the YouTube commercials that they watch. This could be beneficial since audiovisual materials have been proven to be good media to promote students’ fun and active learning. From the above explanation it could be inferred that this present study is aimed at enriching students’ vocabulary knowledge through the language of advertising on YouTube commercial videos. It is a case study. The purpose of the present research is to identify the use of language of advertising on YouTube commercial videos to enrich students’ vocabulary knowledge. The research instruments which will be used are observation, pre-test and post-test. The results of this study are students showed positive perceptions towards the use of YouTube commercial videos to enrich their vocabulary knowledge in English for Advertising class. The study also reveals that the use of YouTube commercial video in teaching and learning English gives positive impact to students’ English vocabulary acquisition and helpful for lecturer in delivering the topic to students.